Colourimetric and fluorescent detection of oxalate in water by a new macrocycle-based dinuclear nickel complex: a remarkable red shift of the fluorescence band() - Rhaman, Md Mhahabubur (2014)
A new macrocycle-based dinuclear nickel chemosensor selectively binds oxalate anions both in solution and the solid state, displaying a remarkable red shift of the fluorescence band with a visible colour change in water at physiological pH in the presence of an external dye.